Is Anesthesia an attractive career choice for undergraduates and young doctors of Pakistan? - Aftab Hussain, Rehana Feroze, Khursheed Hassan Leghari, Faisal Wahid, Aijaz Ali, Abdul Khalique (Journal of Rawalpindi Medical College, 2022)
Objective:To evaluate the factors that act as a barrier for medical students and young doctors inPakistan to choose anesthesia as a career choice. Study design:Cross-sectional study. Study settings:CMH Lahore.Study duration: From January toJune 2021. Materials and Methods:A total of 163 medical students and house officers who were on rotation in operation theatre in various specialties were recruited for this study. A questionnaire was distributed to all the participants. Participants had to select theirspecialty of choice and the reason for not choosing anesthesia. They also had to choose the most important factor for choosing the specialty and the person who influenced them the most to choose the specialty. Results:Only 10 (6.1%) participants chose the anesthesia specialty for their post-graduation, out of these ten, 5 (50%) were male and 5 (50%) were female. The most commonly chosen option {62 (54.87%)} for not selecting anesthesia was “no personal interest”. In response to “What is the most important factor while choosing a specialty?” most of the participants (55%) chose the option “Scope of the specialty”. In response to “Who had the most influence in choosing a specialty?” most of the participants {63 (38.7%)} chose the option “Teachers of the clinical rotations”. Conclusion:It is concluded in our study that only a very small number of students and young doctors willingly opt for anesthesia for their post-graduation which results in a shortage of workforce in this specialty. It is recommended that anesthesia rotation be made compulsory and that the barriers tomentorship in anesthesia be properly addressed. Keywords:Anesthesia, career choice, Influencing factors, specialty, workforce.